Proposals for improving the situation in the education of Roma children based on the opinion of Roma and non-Roma parents - Simić, Nevena D. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2022)
The article deals with education as one of the key factors for better social integration and improvement of living conditions of the Roma population. The research is focused on the attitudes of parents of Roma and non-Roma children in order to find concrete solutions to overcome the problem of education of Roma children in the municipality of Ub. The research included 55 parents of non-Roma children, 50 parents of Roma children and three parents of Roma children with disabilities. The results show that Roma children need support in terms of education from an early age, that it is important to raise the awareness of Roma parents and children about the need for education, that parents must be involved in school events and the child’s progress. Greater engagement of teaching staff is needed in order for everyone in the school environment to feel equal, to enable education that would qualify them for working with Roma children, and to adapt teaching materials to the needs of children. Children from the majority community need basic knowledge of Roma culture to help Roma peers integrate more easily.